2018
DOI: 10.3390/w10010033
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic and Water Quality Evaluation of a Permeable Pavement and Biofiltration Device in Series

Abstract: Two stormwater control measures (SCMs) installed in series were monitored for their individual impact on the hydrology and water quality of stormwater runoff from a 0.08-hectare watershed in Fayetteville, North Carolina, for 22 months. Runoff was first treated by permeable interlocking concrete pavement (PICP), the underdrain of which discharged into a proprietary box filter (Filterra ® biofiltration) which combined high-flow-engineered media with modest biological treatment from a planted tree. Due to a deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…There is also a need to select the best materials for the subgrade of the PICP system so that it can decrease the more rainfall runoff as well as to enhance the infiltrated water quality. In the future, to enhance the PCIP system in terms of rainfall runoff quantity and quality performance, it is necessary to combine the PICP system with other suited LID facilities [26] in such a way that it can provide multiple benefits (hydrological + water quality improvements) in the urban area.…”
Section: Rainfall Events Runoff Volume Reduction Performancementioning
confidence: 99%
See 1 more Smart Citation
“…There is also a need to select the best materials for the subgrade of the PICP system so that it can decrease the more rainfall runoff as well as to enhance the infiltrated water quality. In the future, to enhance the PCIP system in terms of rainfall runoff quantity and quality performance, it is necessary to combine the PICP system with other suited LID facilities [26] in such a way that it can provide multiple benefits (hydrological + water quality improvements) in the urban area.…”
Section: Rainfall Events Runoff Volume Reduction Performancementioning
confidence: 99%
“…Infiltration of the underlying subgrade soil was the main factor for the rainfall runoff reduction through the PICP. Every rain event, hydrological properties for the inflow (INFLOW), PICP outflow (OUTFLOW) after infiltration the outflow runoff and peak flow reduction were calculated by using the volume reduction (VR, Equation (1) [26]), and the peak flow reduction (QR, Equation (2) [26]) as shown below.…”
Section: Runoff Reduction Performance Of Picp Systemmentioning
confidence: 99%
“…Hatt et al [8] investigated the TSS removal efficiency of three field-scale biofiltration systems in two different climates, and concluded that TSS was effectively removed with load reductions generally in excess of more than 90%. Braswell et al [9] indicated that the TSS removal efficiency of a series consisting of permeable interlocking concrete pavement and a proprietary box filter reached 96%. Abdollahian and Kazemi [10] pointed out that the TSS removal efficiency of permeable pavement was in the range of 47-69%.…”
Section: Introductionmentioning
confidence: 99%
“…Urban areas are constantly looking for ways to reduce runoff, and subsequently the pollutants. Proposed solutions, which are generally termed storm water control measures, include bio retention, swales, storm water wetlands and permeable pavements and among these; permeable structures are the most favoured [5]. This is because of their multi-purpose functions such car parking.…”
Section: Introductionmentioning
confidence: 99%